Step
*
1
1
2
1
of Lemma
omega-dark-shadow
1. a : ℕ+
2. b : ℕ+
3. c : ℤ
4. d : ℤ
5. ((a - 1) * (b - 1)) ≤ ((a * d) - b * c)
6. 0 ≤ ((a - 1) * (b - 1))
7. (b * c) ≤ (a * d)
8. j : ℤ
9. (a * b) * j < b * c
10. (b * c) ≤ ((a * b) * (j + 1))
11. (b * c) ≤ ((a * b) * (j + 1))
⊢ ((a * b) * (j + 1)) ≤ (a * d)
BY
{ (SupposeNot THEN (Assert a * d < (a * b) * (j + 1) BY Auto) THEN Thin (-2)) }
1
1. a : ℕ+
2. b : ℕ+
3. c : ℤ
4. d : ℤ
5. ((a - 1) * (b - 1)) ≤ ((a * d) - b * c)
6. 0 ≤ ((a - 1) * (b - 1))
7. (b * c) ≤ (a * d)
8. j : ℤ
9. (a * b) * j < b * c
10. (b * c) ≤ ((a * b) * (j + 1))
11. (b * c) ≤ ((a * b) * (j + 1))
12. a * d < (a * b) * (j + 1)
⊢ ((a * b) * (j + 1)) ≤ (a * d)
Latex:
Latex:
1.  a  :  \mBbbN{}\msupplus{}
2.  b  :  \mBbbN{}\msupplus{}
3.  c  :  \mBbbZ{}
4.  d  :  \mBbbZ{}
5.  ((a  -  1)  *  (b  -  1))  \mleq{}  ((a  *  d)  -  b  *  c)
6.  0  \mleq{}  ((a  -  1)  *  (b  -  1))
7.  (b  *  c)  \mleq{}  (a  *  d)
8.  j  :  \mBbbZ{}
9.  (a  *  b)  *  j  <  b  *  c
10.  (b  *  c)  \mleq{}  ((a  *  b)  *  (j  +  1))
11.  (b  *  c)  \mleq{}  ((a  *  b)  *  (j  +  1))
\mvdash{}  ((a  *  b)  *  (j  +  1))  \mleq{}  (a  *  d)
By
Latex:
(SupposeNot  THEN  (Assert  a  *  d  <  (a  *  b)  *  (j  +  1)  BY  Auto)  THEN  Thin  (-2))
Home
Index